Efecto del estrés calórico en la producción de vacunos de leche, raza Holstein en el Establo “Santa Cecilia” Huanchaco - Mariños Cusquisiban, Luciana (2019)
The present study was conducted with the objective of determining the effect of caloric stress in milk cattle; Likewise, verify the effect of caloric stress on the production of milk in cattle, evaluate the productive parameters, under conditions of caloric stress, and calculate the productivity of dairy cattle, under conditions of caloric stress. The study was carried out in the “Santa Cecilia” stable, located in Alto Huanchaco, district of Huanchaco, province of Trujillo, in the department of La Libertad, from January to April, during the years 2017, 2018 and 2019. The statistical method used It was the descriptive. The methodology was based on calculating the average milk production under conditions of caloric stress. The results obtained are: the average milk production in 2017 was 38.45L, from 2018, 41.31 L and from 2019, 41.6 L. Finally, it is concluded that caloric stress causes large losses in milk production, if not relevant measures are taken; Thus, in the “Santa Cecilia” stable, the loss has been around 5 liters of milk per animal, corresponding to the year 2017.